Physics-based estimates of drag coefficients for the impact pressure calculation of dense snow avalanches. (1st March 2022) - Kyburz, M.L.; Sovilla, B.; Gaume, J.; Ancey, C.
Abstract: In avalanche engineering and hazard mapping, computing impact pressures exerted by avalanches on rigid structures has long been a difficult task that requires combining empirical equations, rules of thumb, engineering judgment and experience. Until the 1990s, well-documented avalanches were seldom, and the main source of information included back-analysis of damage to structures and scarce field measurements. By the 1990s, several field sites were equipped across Europe, and since then they have provided new insights into the physics of impact. The main problem has been the difficulty in interpreting and generalizing the results to propose sound methods for estimating impact pressure. Testing a wide range of flow conditions has also been difficult in the field. To go a step forward in the elaboration of new guidelines for computing avalanche forces, we developed a numerical code based on the Discrete Element Method (DEM), which made it possible to simulate how an avalanche interacts with a rigid obstacle and to study how impact pressure depends on obstacle shape and size, as well as the avalanche flow regime. We extracted pressure and velocity data from the Vallée de la Sionne database to validate the DEM code, calibrate the model parameters, and elaborate avalanche scenarios. We studied four avalanches scenarios related to distinct flow regimes of the avalanche's dense core. In these scenarios, snow cohesion and velocity were imposed at the upstream boundary of the computational domain. Building on earlier work, we generalized an empirical equation for computing impact pressure as a function of snow cohesion, velocity, flow regime, and structure shape and size. Various coefficients were defined and calibrated from our DEM data. Within the range of tested values, we found good agreement between estimated pressure and field data. Highlights: Impact pressure on obstacles mostly decreases with increasing obstacle width. Local impact pressure concentrations may occur at the obstacle's outer edges and the leading edge. We propose a novel, physics-based method to estimate drag coefficients. With this method the pressure can be calculated for diverse flow regimes. Using this method, we find good agreement with field pressure measurements.